A novel approach for rapid discrimination of common and durum wheat flours using spectroscopic analyses combined with chemometrics. (July 2021) - Unuvar, A.; Boyaci, I.H.; Koksel, H.
Abstract: Spectroscopic methods were used in this study for the discrimination of durum and common wheat samples since they are rapid, reliable, easy to use, low cost, environmentally friendly, and non-destructive. For this purpose, 120 common and 119 durum wheat samples with different genotypes were collected from various regions in Turkey and analysed using Raman spectroscopy, near-infrared spectroscopy (NIR), synchronous fluorescence spectroscopy (SFS), and attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR). Data analysis was performed using the principal component analysis (PCA) and partial least squares-discriminant analysis (PLS-DA). These spectroscopic tools, combined with chemometric analysis, were generally successful in distinguishing common and durum wheat flour samples. It was found that the best method was SFS with a discrimination rate of 100% based on high sensitivity (1.000) and specificity (1.000) values. The effectiveness of the models in which NIR and ATR-FTIR spectroscopies were used was found to be highly similar in terms of the discrimination of durum and common wheat samples. Data obtained from Raman Spectroscopy demonstrated that the method was less sensitive in discriminating between common and durum wheat flour samples than the other spectroscopic techniques with a quite high RMSEP value (0.441). SFS, ATR-FTIR, and NIR spectroscopies proved to be more sensitive and applicable tools than Raman spectroscopy in the discrimination of common and durum wheat samples. Graphical abstract: Image 1 Highlights: Discrimination of wheat flour was by spectroscopic methods quite successfully. Synchronous fluorescence spectroscopy was the best method for wheat classification. NIR, and ATR-FTIR spectroscopies were able to distinguish wheat samples quite clearly. PLS-DA gave better results than PCA in chemometric analysis.